An Analysis of Internal Audit Investment Among Top Malaysian Listed Companies - Naimi Mohamad Nor, Mohamad; Ishak, Suhaimi (KnE Social Sciences, 2019)
The importance of internal audit function in improving the company’s internal control risk management and corporate governance has been emphasized in the Malaysian Code of Corporate Governance (MCCG) and Bursa Malaysia Listing Requirements. Based on the Listing Requirements, Malaysian listed companies are required to establish the internal audit function, which is independent and this function must be supervised by the audit committee. Although the importance of internal audit function has been highlighted in various code of corporate governance, little is known about the investment made by the company in internal audit activity. This study capitalizes the publicly available data on internal audit cost and the type of internal function provider in Malaysia setting. The primary purpose of this study is to describe internal audit practices, especially on the internal audit budget in Malaysia for the year 2017 for top 300 companies. Based on the descriptive analysis, it is found that the internal audit fee is relatively lower than the cost of external audit and most of the companies’ internal audit function was carried out by in house teams. Also, the benefit from economies of scale is less pronounced in internal audit as compared to external audit services. Some further analyses were also conducted, and the article is ended recommendations for future research to be undertaken in investigating the internal importance audit in Malaysia.